Additional guarantees of the tax penalty - Yassin Al-taie; Zainab Jassim (الرافدین للحقوق)
Tax legislation has increasingly focused on stipulating certain basic guarantees necessary to achieve adequate tax revenue during the process of determining income tax, collecting it, and transferring it to the public treasury. To this end, the tax administration has been granted broad powers, including the imposition of stricter tax penalties on taxpayers. The severity of the penalty is considered one of the most important guarantees established by tax legislation to safeguard the state's interest in collecting tax debts. These guarantees include those that are standard and necessitated by the existence of tax penalties, deriving from the general principles governing the imposition of taxes, as well as those specifically enacted by the legislator to ensure the state’s right to impose tax punishment. Hence arises the concept of additional guarantees for the tax penalty.